A common positive trans-acting factor binds to enhancer sequences in the promoters of mouse H-2 and beta 2-microglobulin genes. - Israël, A (Proc Natl Acad Sci U S A, 1987)
Using gel retardation and in vitro "footprinting", we have analyzed the interactions between nuclear proteins derived from various mouse cells and the enhancer and interferon response sequences of the H-2Kb gene. We have found that a protein factor binds a site in the enhancer sequence that partially overlaps the interferon response sequence. This factor also binds to a similar sequence lying in the opposite orientation in the promoter of the mouse beta 2-microglobulin gene, suggesting a common regulatory mechanism. Transfection competition experiments indicate that this factor acts as a positive element in the expression of H-2 and beta 2-microglobulin genes. IMAGES: